Enhancing Professional Communication Through English For Specific Purposes : Curriculum Design, Pedagogy, And Technological Integration - Elda Marta Suri (LPPM Universitas Ekasakti, 2024)
This study aims to explore the implementation of English for Specific Purposes (ESP) in addressing the unique linguistic and professional needs of specific fields, such as business, healthcare, engineering, and tourism. The research adopts a mixed-method approach, combining qualitative interviews with ESP practitioners and quantitative analysis of student performance. Key findings highlight the effectiveness of contextualized learning materials and task-based instruction in enhancing learners' proficiency and workplace readiness. The study concludes with recommendations for curriculum design and pedagogical strategies that align with the dynamic demands of various industries. These insights contribute to advancing the role of ESP in bridging the gap between academic preparation and professional practice.